Anomalies in Finance Stocks Market: Momentum Effect and Return Reversal - Kok, Sook ching; Qaiser Munir; Hooi, Hooi Lean (2018)
This study applies relative strength trading rule to analyse momentum effect and return reversal in the finance sector of Malaysia for the period of January 1997–December 2014. We construct J/K overlapping portfolios consisting of finance stocks over 1–12 months short investing horizons The estimated average cumulative monthly excess returns from momentum strategy portfolios are in the range of 0.017–0.023, while contrarian strategy portfolios are between 0.023 and 0.029 (in percentage). The market-adjusted returns cannot be explained based on the market risk factor of Capital Asset Pricing Model (CAPM). The findings indicate short-run inefficiency in the weak-form sense.